The Role of Work Discipline in Mediating the Relationship between Leadership and Organizational Culture on Employee Performance at the Regional Office of the Ministry of Religion of North Sumatra Province - Ayu Alzahra, Hilda; Rahayu, Sri (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2025)
This study aims to examine the direct and indirect effects of leadership and organizational culture on employee performance, with work discipline as a mediating variable. The study was conducted in 2025 at the Regional Office of the Ministry of Religious Affairs of North Sumatra Province, involving 65 respondents from a total of 185 employees selected through purposive sampling based on the Slovin formula. Primary data were collected using a questionnaire and analyzed using a quantitative-associative approach through the SEM-PLS method using the SmartPLS 3 application. The results of the analysis show that leadership and organizational culture have a positive and significant effect on work discipline, but do not directly affect employee performance. Conversely, work discipline has a significant effect on performance. Organizational culture is a dominant factor in shaping work discipline, while work discipline is the main determinant of performance. Indirectly, leadership and organizational culture affect performance through work discipline. This research model explains 72.6% of the variation in work discipline and 73.3% of the variation in employee performance.